Numerical Study on Flow and Heat Transfer Mechanisms in the Heat Exchanger Channel with V-Orifice at Various Blockage Ratios, Gap Spacing Ratios, and Flow Directions. (28th April 2019) - Boonloi, Amnart; Jedsadaratanachai, Withada
Abstract : Numerical assessments in the square channel heat exchanger installed with various parameters of V-orifices are presented. The V-orifice is installed in the heat exchanger channel with gap spacing between the upper-lower edges of the orifice and the channel wall. The purposes of the design are to reduce the pressure loss, increase the vortex strength, and increase the turbulent mixing of the flow. The influence of the blockage ratio and V-orifice arrangement is investigated. The blockage ratio, b / H, of the V-orifice is varied in the range 0.05–0.30. The V-tip of the V-orifice pointing downstream (V-downstream) is compared with the V-tip pointing upstream (V-upstream) by both flow and heat transfer. The numerical results are reported in terms of flow visualization and heat transfer pattern in the test section. The thermal performance assessments in terms of Nusselt number, friction factor, and thermal enhancement factor are also concluded. The numerical results reveal that the maximum heat transfer enhancement is found to be around 26.13 times higher than the smooth channel, while the optimum TEF is around 3.2. The suggested gap spacing for the present configuration of the V-orifice channel is around 5–10%.